Imaging Characteristics Associated with Clinical Outcomes in Posterior Reversible Encephalopathy Syndrome - Schweitzer, Andrew D (Neuroradiology, 2017)
PURPOSE: Posterior reversible encephalopathy syndrome (PRES) is a disorder of cerebrovascular autoregulation that can result in brain edema, hemorrhage, and infarction. We sought to investigate whether certain imaging characteristics in PRES are associated with clinically significant patient outcomes. METHODS: We retrospectively reviewed all cases of PRES occurring between 2008 and 2014 at two major academic medical centers. Demographic, clinical, and radiographic data were collected. We analyzed imaging studies for vasogenic edema, hemorrhage, and diffusion restriction. We performed univariate analysis and stepwise logistic regression to assess the association between our radiologic findings of interest and clinical outcomes as defined by hospital discharge disposition and modified Rankin scale (mRS) at time of discharge. RESULTS: We identified 99 cases of PRES in 96 patients. The median age was 55 years (IQR 30-65) and 74% were women. In 99 cases, 60% of patients had active cancer, 19% had history of bone marrow or organ transplantation, 14% had autoimmune disease, and 8% were peripartum. Imaging at clinical presentation showed extensive vasogenic edema in 39%, hemorrhage in 36%, hemorrhage with mass effect in 7%, and restricted diffusion in 16%. In our final logistic regression models, the presence of extensive vasogenic edema, hemorrhage with mass effect, or diffusion restriction was associated with worse clinical outcome as defined by both discharge disposition (OR=4.3; 95% CI: 1.4-36.3; p=0.047) and mRS (OR=3.6; 95% CI: 1.2-10.7; p=0.019). CONCLUSIONS: Extensive vasogenic edema, hemorrhage, and restricted diffusion on initial imaging in PRES are associated with worse clinical outcomes.